Living with dinosaurs - Lauber, Patricia; Henderson, Doug (New York : Bradbury Press ; Toronto : Collier Macmillan Canada ; New York : Maxwell Macmillan International Pub. Group, 1991)
Recreates life among the dinosaurs living in North America seventy-five million years ago.
Includes index.
Keywords: Dinosaurs; Dinosaurs